Short carbon fiber-reinforced epoxy tribomaterials self-lubricated by wax containing microcapsules - Tang, Xiu-zhi (2014)
The effects of wax lubricant filled microcapsule content on the tribological properties of epoxy composites without or with 8 wt.% short carbon fibers (SCFs) were systematically investigated. The core percentage of the microcapsules used in this study was about 70 wt.%. The tribological results clearly showed that the friction and wear of the epoxy composites without or with SCFs tested against a 6 mm steel ball significantly decreased with increased microcapsule content from 2.5 to 10 wt.% as a result of the increased amount of released wax lubricant to lubricate rubbing surfaces. The epoxy composites with 8 wt.% SCFs exhibited the lower friction and wear than the ones without SCFs due to the combined lubricating effects of SCFs and released wax lubricant and the improved mechanical strength of the composites. It can be concluded that the higher microcapsule content gives rise to the lower friction and wear of the epoxy composites as the epoxy composites with 8 wt.% SCFs have the better tribological performance than the ones without SCFs.